Implementasi Psikoedukasi Guru PAI dalam Pembelajaran pada Siswa Broken Home di Sekolah Dasar Islam Terpadu An-Nafis Teluk Mengkudu - Muti Husnul Khotimah; Rizky Arafani Nurhikmah Marpaung; Rizka Harfiani (Yayasan Haiah Nusratul Islam, 2026)
The phenomenon of broken homes can affect the psychological development and learning processes of elementary school students, leading to low motivation to learn, difficulty managing emotions, lack of self-confidence, and obstacles in social interaction. These conditions call for the active role of teachers particularly Islamic Religious Education (PAI) teachers in providing guidance through a psychoeducational approach. This study aims to describe the implementation of psychoeducation by PAI teachers in teaching students from broken homes and to identify the obstacles faced at SD IT An-Nafis Teluk Mengkudu. The study employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results indicate that psychoeducation was implemented through interpersonal communication, motivational support, fostering religious practices, emotional support, showing Islamic videos, sharing activities, and collaboration with homeroom teachers and parents. This implementation had a positive impact on students’ emotional development, learning motivation, and social skills. However, its implementation still faces obstacles in the form of students’ unstable emotional states, time constraints, a lack of family support, and teachers’ limited competencies in the field of psychology.